Location-based information systems : developing real-time tracking applications - Labrador, Miguel A.; Perez, Alfredo Jose; Wightman, Pedro M. (Chapman & Hall/CRC computer and information science series, 2011)
"The book provides a comprehensive introduction to developing location-based information systems based on GPS-enabled cellular phones. It describes all of the components needed to develop a location-based information system and provides readers with the opportunity to build an example application. Chapters cover obtaining a user?s location, storing and retrieving data, communicating over a network, Java ME Web services, and visualizing data. In the theoretical chapters, the authors address location provider architectures, the hardware and software architecture of a mobile phone, the Java ME platform, and other important programming aspects for mobile phones".